Process system resilience: from risk management to business continuity and sustainability. (4th March 2020) - Jain, Prerna; Pasman, Hans J.; Mannan, M. Sam
In general, by competition, energy efficiency, reduced staff, etc. process safety and risk management challenges have increased with a heavier focus of public perception on risks globally. This has necessitated exploring tools for transition from the narrower to a broader approach with goals of business continuity and sustainability for risk management. The application of resilience engineering is being explored for considering the dynamics of socio-technical aspects. This paper presents the systems-based resilience approach for risk management in the process industry and provides a description of process system architecture, functional requirements, and life cycle stages. This paper introduces the process resilience analysis framework (PRAF) and its four aspects. As an example, the 2012 Chevron Richmond Refinery incident is reviewed, and relationship is established between resilience and sustainability. The conclusion is drawn that using PRAF strengthens the resilience capabilities of a process system to foster business continuity and sustainability.